Survey of Living Conditions in the Arctic: Inuit, Saami and the Indigenous Peoples of Chukotka (SLICA) - Andersen, Thomas; Kruse, Jack; Poppel, Birger (ARCTIC, 2002)
Arctic scientists wrote, in the 1998 Opportunities in Arctic Research: Final Report for the U.S. National Science Foundation, "For the last few decades the scientific community has expressed concern about the vulnerability of the Arctic and its residents to environmental, social, and economic changes . [Recent] research results show that arctic climate and ecosystems are indeed changing substantially with impacts on people living in and outside the Arctic." The scientists listed as the first key question, "How are the rapid social, political, economic and environmental changes occurring in the Arctic today affecting the people there? . Delegates to the 1998 Inuit Circumpolar Conference (ICC) passed a resolution supporting an international survey of living conditions in the Arctic. The resolution noted, "Rapid social change characterises all indigenous peoples of the Arctic . There is a need to document and compare the present state of living conditions and the development among the indigenous peoples of the Arctic." This essay presents a comparative study of living conditions among the Inuit and Saami peoples of the United States, Canada, Greenland, Norway, Sweden, and Finland and the indigenous peoples of the Kola and Chukotka Peninsulas in Russia. The main scientific institutions behind SLICA are Statistics Greenland; the Department of Political Science, University of Tromsø, Norway; the Centre for Research in International Migration and Ethnic Relations, University of Stockholm, Sweden; the Arctic Centre, University of Lappland, Finland; the Barents Centre for Social Research, the Kola Peninsula, Russia; the Russian Association of Indigenous Peoples of the North, Moscow, Russia; the Institute of Social and Economic Research, University of Alaska, Anchorage, U.S.A.; and the Groupe d'études inuit et circumpolaires (GÉTIC) of Laval University, Quebec City, Canada. The main indigenous organizations working with SLICA are ICC, the Saami Council and the Russian Association of Indigenous Peoples of the North. The ...